Examining the Access to Resources and Gender Disparities in the Community (International Journal of Scientific Research in Science and Technology, 2026)
This study examined access to resources and gender disparities within communities in Ghana, with particular attention to how unequal access affects participation in development and sustainable outcomes. The study adopted a mixed method research approach using the explanatory sequential design, which allowed for the integration of quantitative findings with qualitative explanations. With a sample size of 112, data were collected from government officials, policymakers, community members, women and men engaged in development activities, as well as leaders of non-governmental organisations involved in gender equality and sustainable development initiatives. Purposive sampling was employed to select respondents with relevant knowledge and experience on gender and resource-related issues. Quantitative data were gathered through structured questionnaires, while qualitative data were obtained through interviews and focus group discussions. The quantitative data were analysed using descriptive statistics, whereas qualitative data were analysed using thematic analysis. The findings reveal persistent gender disparities in access to key resources such as education, healthcare, land, financial services, economic opportunities, and decision-making platforms. Women were found to face greater structural and socio-cultural barriers compared to men, particularly within traditional and rural community settings. These disparities limit women’s economic empowerment, agency, and participation in leadership, thereby constraining overall community development. The study concludes that equitable access to resources is central to promoting gender equality, strengthening human capital, and achieving sustainable community development in Ghana. It therefore recommends the implementation of gender-responsive policies, reforms in land and financial systems, and targeted interventions to enhance women’s participation in economic and governance processes at the community level.